(untitled) (Моделювання, керування та інформаційні технології, 2023)
This article offers an in-depth examination of scheduling strategies in container orchestration systems, emphasizing the importance of selecting the most suitable strategy for a system’s specific needs. The article explores the evolution of container systems and challenges around cloud reliability and fault tolerance. A structured experimental methodology was introduced to compare different strategies systematically, utilizing various testing methods like packing until first rejection, packing until the cluster is full, and introducing different malfunctions such as liveness and network partitioning. Comparative results between the “binpack” and “spread” strategies highlighted that while the former excels in higher scheduling requests acceptance rate, the latter is superior in offering higher availability. The findings show the need for aligning the scheduling strategy with system objectives, be it resource optimization, fault tolerance or other desired characteristics